(untitled) (Olhar de Professor, 2021)
This article presents a brief reflection of two primary education teachers considering possibilities and challenges during the COVID-19 pandemic caused by the new coronavirus. In order to discuss the teaching-learning process in this context, it is based on the experience of 11 weeks of teaching mediated by technologies in the subjects of Physical Education and Arts in the early years of elementary school in a private educational institution in the Federal District, Brazil. It aims to initiate a discussion about the changes experienced in education during this period and their possible future implications.